Sliding mode control of the DFIG used in wind energy system - Glaoui, H.; Harrouz, A. (Електротехніка і електромеханіка, 2018)
This paper, presents the application of the direct vector control using the sliding mode control (SMC) on the doubly fed induction generators (DFIG). The synthesis of the control laws is based on the model obtained by the orientation of the stator flux. The active and reactive powers that are generated by the doubly fed induction generators will be decoupled by the orientation of the stator flux and controlled by sliding mode controllers that have been developed. In order to rule on the validity as well as the performance of this type of adjustment, we will check its robustness by varying some parameters of the machine doubly fed induction